Critical role of intracellular RyR1 calcium release channels in skeletal muscle function and disease - Hernández-Ochoa, Erick O.; Pratt, Stephen J.; Lovering, Richard M.; Schneider, Martin F. (Frontiers in Physiology, 2016)
The skeletal muscle Ca2+ release channel, also known as ryanodine receptor type 1 (RyR1), is the largest ion channel protein known and is crucial for effective skeletal muscle contractile activation. RyR1 function is controlled by Cav1.1, a voltage gated Ca2+ channel that works mainly as a voltage sensor for RyR1 activity during skeletal muscle contraction and is also fine-tuned by Ca2+, several intracellular compounds (e.g., ATP), and modulatory proteins (e.g., calmodulin). Dominant and recessive mutations in RyR1, as well as acquired channel alterations, are the underlying cause of various skeletal muscle diseases. The aim of this mini review is to summarize several current aspects of RyR1 function, structure, regulation, and to describe the most common diseases caused by hereditary or acquired RyR1 malfunction.